CHINESE DOMESTIC TOURISM The Double Influence of The Politics (Policy) and The Nature - Komang Ratih Tunjungsari (Institut Pariwisata dan Bisnis Internasional, 2013)
Nowadays, one of the Asian’s tiger in economy, The People’s Republic of China (PRC) not only developing their economy through a pure industrialization as we can found in Mao’s Era. When we throw back into the Deng Xiao Ping’s era, PRC announced its new policy that is ready to face the new world, called the Open Door Policy. According to the policy, tourism became one of the alternatives to increase the economy after suffered from Mao’s era. Furthermore, the term of tourism in China is not restricted as the businesses travel, as pilgrimage or as wellness business. Afterwards, tourism became a need, not only a want toward the Chinese citizen and grown up into the development of domestic tourism. The government of the PRC do their effort in accommodate the need of the citizen of tourism by bridging the tourism policy through manage the potential of the nature and giving the sufficient accessibilities to built the proper tourism destination.